Evaluation of the cool-down behaviour of ITER FW beryllium tiles for an early failure detection. (December 2016) - Weber, Thomas; Bürger, Andreas; Dominiczak, Karsten; Pintsuk, Gerald
Highlights: The plasma facing Be tiles in ITER may detach from the supporting structure and overheat if the joint quality and performance were poor. Nevertheless, when a heat flux is applied the temperature gradient causes a bending of the tile. This bending can actually close the gap/crack so that the thermal conductivity is restored again. Thermo-mechanical FEM simulations demonstrate this principle and its influence on the cool-down. For practical reasons the use of an exponential fitting function is actually a good choice. Abstract: The design of the first wall in ITER foresees several hundred thousand beryllium tiles, which are bonded to the water-cooled CuCrZr supporting structure. Due to the nature of a Tokamak reactor this bonding is faced to thermal fatigue. Since the failure of a single tile might already have a major impact on the operability of ITER, comprehensive high heat flux tests are performed on prototypes prior to the acceptance of manufacturing procedures. For a deeper understanding of the temperature curves, which were and will be measured by IR devices of these first wall prototypes, thermo-mechanical FEM simulations shall demonstrate the possibilities of an early bonding failure detection. Hereby, the maximum temperatures for each cycle as well as the cool-down behaviour are the input data.